(untitled) (Journal of Asian Development Studies, 2026)
Forest fragmentation, driven by climate change, urbanisation, deforestation, and land-use changes, significantly impacts carbon storage in forest ecosystems. This study investigates carbon density variations in fragmented moist temperate forests across altitudinal gradients in the Malakand Division, Swat, Pakistan, focusing on both vegetation and soil carbon dynamics within forest interior and edge zones. Stratified random sampling was conducted at five elevations (1500, 1700, 1900, 2100, and 2300m) to capture comprehensive data on above-ground biomass (AGB), below-ground biomass (BGB), and soil carbon stocks. Results indicated that interior forest zones consistently exhibit higher total carbon density 1200 ± 50 tCha⁻¹ compared to exterior zones 800 ± 40 tCha⁻¹. Soil carbon content also showed a significant interior-exterior gradient, with total soil carbon storage reaching 740 ± 10 tCha⁻¹ in the interior while 670 ± 8 tCha⁻¹ in the exterior zones. Species-specific analysis revealed that larger tree diameters are associated with higher carbon sequestration, particularly in species such as Cedrus deodara and Abies pindrow, which reach mean carbon densities of>150 tCha⁻¹ and <200 tCha⁻¹, respectively, in the forest interior. This research underscores the importance of both vegetation and soil carbon contributions within forest interiors and recommends targeted conservation and restoration strategies to optimise carbon sequestration, thereby enhancing climate mitigation potential